2000
DOI: 10.1093/intimm/12.9.1267
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ Valpha14 NKT cells play a crucial role in an early stage of protective immunity against infection with Leishmania major

Abstract: The roles of gamma delta T, NK and NKT cells in an early stage of protective immunity against infection with Leishmania major were investigated. Further, the contribution of these innate cells to the expression of 65 kDa heat shock protein (HSP65) in host macrophages was examined, since we found previously that this expression prevents apoptotic death of infected macrophages and is a crucial step in the acquisition of protective immunity against infection with various obligate intracellular protozoa including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
2
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 27 publications
1
69
2
1
Order By: Relevance
“…It has been shown that NKT cells play a crucial role in an early stages of protective immunity against infection with Leishmania major in mice (19). It has also been recently described that a subset of murine NKT cells is activated during L. donovani infection (20).…”
Section: Endritic Cells (Dcs)mentioning
confidence: 99%
“…It has been shown that NKT cells play a crucial role in an early stages of protective immunity against infection with Leishmania major in mice (19). It has also been recently described that a subset of murine NKT cells is activated during L. donovani infection (20).…”
Section: Endritic Cells (Dcs)mentioning
confidence: 99%
“…[29][30][31] and Toxoplasma gondii [32,33]. A 65 kDa heat-shock protein (HSP65) was found to be up-regulated in macrophages after infection by these organisms [34,35] and Trypanosoma cruzi [36], but its relevance to the infection remains unknown. Many viral infections, such as hepatitis C are known to confer fas ligand-specific signals on the host cells for apoptosis [37], whereas T. cruzi infection inhibits this [38].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in mice have revealed that a-GalCer treatment promotes resistance against infections, tumours and autoimmunity [15][16][17][18][19][20][21][22][23][24][25][26][27]. In a murine vaccination study, a-GalCer potentiated protective immune responses induced by malaria vaccines [28].…”
Section: Introductionmentioning
confidence: 99%